Interpreting Contemporary Art : The Finnish National Gallery Annual Publication. - Hannula, Mika; Jaukkuri, Maaretta; Nyberg, Patrik; The Finnish National Gallery, Helsinki; Ateneum Art Museum, Helsinki (Helsinki : Finnish National Gallery, 1998)
Duchamp, Marcel ; Cragg, Tony (Anthony) ; Warhol, Andy ; Beuys, Joseph ; Roos, Nina ; Richter, Gerhard ; Raetz, Markus ; Christiansen, Björnstjerne ; Fenger, Jacob ; Nielsen, Rasmus ; Gonzalez-Torres, Felix ; Törrönen, Anssi ; Masaccio ; Johns, Jasper ; Hirst, Damien ; Rembrandt ; Ballet, Elisabeth ; Aalto, Johanna ; Tandberg, Vibeke
Engels & Fins
boek